Education and Social Change on the Use of Online Learning Media - Sari, Aulia; Faelasup (Kirana Publisher (KNPub), 2024)
The more sophisticated technology is today, the learning process can also become more sophisticated with the internet that can be accessed anytime and anywhere to help facilitate humans, especially the world of education because with the existence of sophisticated technology even though the distance is far apart, you can still do learning by using google meet, zoom and others. So it is not surprising that young children have been given gadjed because almost all learning is accessed using gadjed. The formulation of the problem is (1) How is the role of parents and teachers in the use of online media (2) What are the obstacles faced in online media learning. This research uses qualitative methods with a direct approach to parents and teachers, to find out how the role of parents and teachers to supervise children in the use of online media. So that children are not wrong in using online media. This research aims to find out how the role of parents and teachers in the use of online media and to find out what are the obstacles faced in online media learning. The obstacles are (1) Unstable internet connections are still not active in remote pockets (2) Inadequate Facilities and Infrastructure Technology support devices are clearly expensive (3) Lack of budget because the welfare of students and teachers is rather far from expectations, costs can also be considered problematic (4) Very limited technological information from students and teachers.